Quantum “Ghosts” - Amaral,Gabriela M. (2016)
Can you pick a complex subject in quantum mechanics and discuss it with a minimum number of equations, in a simplified form that the general scientific public could understand? This was a question presented to graduate students of the one-year Quantum Mechanics course based on the text book Modern Quantum Mechanics by J. J. Sakurai and Jim Napolitano, at the State University of Campinas (UNICAMP), Brazil. The first seven authors of this paper are graduate students (alphabetical order) that accepted to try it. The chosen subject was “delocalized quantum states”, and it will be discussed using colloquial terms like quantum ghosts, spooky action, splitting beings and invisibility cloak.